The role of Id1 expression with EGF and EGF-R serum concentration assessment in malignant ovarian tumours - Czekierdowski, Artur; Czekierdowska, Sylwia; Daniłoś, Jarosław; Nowakowski, Andrzej; Stachowicz, Norbert (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: Inhibitors of DNA binding/inhibitors of differentiation (Id) protein family (Id1, Id2, Id3 and Id4) may play an important role in various cancer angiogenesis stimulation through interactions with strong mitogenic and angiogenic factors such as EGF and EGFR. Aim of the study: Our aim was to assess if the expression of Id1 protein with EGF and EGF-R serum concentration assessment is associated with selected epidemiological, clinical and histological features of malignant ovarian tumours. Material and methods: The study group included 95 women operated because of ovarian tumours. In this group, 83 masses proved to be malignant. The findings were correlated with the tumour type, histological grading and tumour FIGO stage. Tumour Id1 protein was assessed by immunohistochemistry and EGF with EGF-R serum concentrations were examined by ELISA. Results: The mean age of the patients was 52.6 ±15.1 years and 43 (45.2%) of women in this group were premenopausal. Histological examination revealed that in the malignant group there were 38 serous ovarian cancers, 23 mucinous cancers, 7 endometrioid cancers and 13 other malignant tumours including 6 metastatic to the ovary. Significant differences were found between concentrations of EGF and EGF-R depending on the patient\'s menopausal status (p = 0.01 and p = 0.002, respectively). Histological grade was significantly correlated with EGF concentrations in women with malignant ovarian tumours (p = 0.01). FIGO stage was also significantly correlated with Id1 expression (p = 0.09) and EGF concentration (p = 0.01). Also, significant correlations were found between Id1 expression, and histological grade and tumour FIGO stage (both p = 0.005). EGF and EGF-R concentrations were significantly correlated with each other (p = 0.008). Moreover, both EGF and EGF-R concentrations were correlated with Id1 expression (p = 0.0005 and p = 0.004, respectively). Conclusion: Our results indicate that Id1 protein and EGF with EGF-R concentration assessment may be used as additional prognostic markers in women with various types of malignant ovarian tumours.